Effects of Educational Intervention on Nurse Leaders’ Knowledge and Perceived Self-Efficacy to Participate in the Health Policy-Making Process: A Study in Nigeria - Ani, Goodman; Okoronkwo, Ijeoma; Nwodoh, Chijioke; Haruna, Habu (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2026)
Background: Participation in shaping health policy is a key nursing role as health policy influences the entire health system. Nurses, being the largest and most reachable health care professionals, are critical in health care outcomes. As patient advocates, nurses are in an advantageous position to advance patient-centred policies, and their involvement in the health policy-making process is crucial. Because health policies have a direct bearing on nursing practice, nurses need to participate in health policy formulation.Aim: This study aimed to determine the effects of educational intervention on nurse leaders’ knowledge and perceived self-efficacy to participate in the health policy-making process.Design: The research design used for the study was quasi-experimental. We adopted a treatment-control approach with before-treatment and after-treatment data collection. A total of 32 nurse leaders were purposively selected from Nigeria’s six geopolitical zones; 81% of the participants had a master’s degree or doctorate in nursing.Method: Participants were recruited and split into control and treatment groups. We used a self-structured questionnaire to collect data from both groups. Educational intervention was administered to the treatment group only. We collected post-treatment data from the control and treatment groups for analysis. Data were analyzed using descriptive and inferential statistics using the Statistical Package for Social Sciences.Results: Educational intervention has a positive effect on nurse leaders’ knowledge of the health policy-making process. We observed an increase from 62.5% of participants having very good knowledge to 100% having very good knowledge. We found a statistically significant difference between the participants’ pre-test and post-test knowledge of the policy-making process (p = 0.001). We also found a significant difference in the control group’s and intervention group’s self-efficacy to participate in the health policy-making process (p = 0.006) after educational intervention.Conclusion: Nurse leaders need focused education on the health policy-making process to increase their involvement and efficacy in the health policy-making process.